Zdravstvena vzgoja svojcev varovanca z demenco na kliničnih oddelkih za klinično psihiatrijo (KOKP) v Ljubljani - Doberšek-Mlakar, Jacinta (Obzornik zdravstvene nege, 1999)
The article describes programmed health education of relatives of demented patients. Basic ingredients of health education support program, its purpose and aims are described, and aims of similar programmes carried out elsewhere presented. The article defines the needs required by such approach, describes dementia and deficiencies in the fields of self care and overall functioning of such patients. The author delineates subject units, and the method of organization and evaluation of such programs of work as a part of a more comprehensive quality research.
Keywords: bolniki; Caregivers; demenca; Dementia; Family; Health education; hospitalizacija; Psychiatric department, hospital; zdravstvena vzgoja